The Usage of Antimicrobials in Pediatric Dentistry- A Narrative Review - Setty, Jyothsna V; S, Shilpa; Srinivasan, Ila (The Journal of Dentists, 2023)
Antimicrobials play a crucial role in pediatric dentistry, helping to manage and prevent infectious diseases. However, their indiscriminate use and misuse can have significant consequences, including the development of antimicrobial resistance. This article aims to provide an in-depth exploration of antimicrobials in pediatric dentistry, discussing their appropriate use, common indications, potential adverse effects, and the importance of judicious prescribing. It also highlights the significance of antimicrobial stewardship programs in promoting responsible antimicrobial use and mitigating the emergence of resistance in dental set up.